2021
DOI: 10.3389/fnmol.2021.788039
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid and Several Neurotransmitters Converge on Rho-Kinase 2 Signaling to Manage Motoneuron Excitability

Abstract: Intrinsic membrane excitability (IME) sets up neuronal responsiveness to synaptic drive. Several neurotransmitters and neuromodulators, acting through G-protein-coupled receptors (GPCRs), fine-tune motoneuron (MN) IME by modulating background K+ channels TASK1. However, intracellular partners linking GPCRs to TASK1 modulation are not yet well-known. We hypothesized that isoform 2 of rho-kinase (ROCK2), acting as downstream GPCRs, mediates adjustment of MN IME via TASK1. Electrophysiological recordings were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, LPA acts as a physiological activator of Rho to activate ROCK through the LPAR receptor [ 43 ], ROCK is a ubiquitously expressed kinase with two known isoforms, ROCK1 and ROCK2 [ 44 ]. ROCK2 mRNA is widely distributed all along with the central nervous system [ 45 ], Interfering with ROCK2 mRNA and downregulating ROCK2 expression can improve neurological diseases including neuropathic pain [ 42 ]. This result is partially consistent with our current finding that LPA (18 : 1)-induced ROCK2 upregulation with less effect on ROCK1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LPA acts as a physiological activator of Rho to activate ROCK through the LPAR receptor [ 43 ], ROCK is a ubiquitously expressed kinase with two known isoforms, ROCK1 and ROCK2 [ 44 ]. ROCK2 mRNA is widely distributed all along with the central nervous system [ 45 ], Interfering with ROCK2 mRNA and downregulating ROCK2 expression can improve neurological diseases including neuropathic pain [ 42 ]. This result is partially consistent with our current finding that LPA (18 : 1)-induced ROCK2 upregulation with less effect on ROCK1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inactivation of FAK was observed in olfactory bulb of APP/PS1 AD mice, while an activation was observed in LOAD patients (Lachen-Montes et al, 2016). ROCK2 (Rho Associated Coiled-Coil Containing Protein Kinase 2) plays a crucial role in motor neuron intrinsic excitability (Garcia-Morales et al, 2021). ROCK2 was also characterized to regulate axonal growth and neuronal death, and, interestingly, it was reported that downregulation is beneficial for neuronal survival (Koch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%